Study on the chemical constituents of Magnolia insignis collected in Tuyen Quang province, Vietnam. Issue 1 (26th February 2020) - Ninh, Pham Thi; Hoai, Ly Thi Thu; Ha, Chu Thi Thu; Thai, Tran Huy; Hang, Phan Dieu; Van Loc, Tran; Thao, Tran Thi Phuong
Abstract: From the leaves of Magnolia insignis, six compounds including (+)‐afzelechin (1), budlein B (2), pinoresinol monomethyl ether‐β‐D‐glucoside (3), nicotiflorin (4), kaempferol‐3‐O‐β‐D‐xylopyranose (5), astragalin (6) were isolated. The structures of these compounds were elucidated by MS and NMR spectra and comparison with the reported data. This is the first time that all of the above compounds have been isolated from Magnolia insignis .